2016
DOI: 10.1177/0267659116676335
|View full text |Cite
|
Sign up to set email alerts
|

Plasma apelin-12 levels may predict in-hospital major adverse cardiac events in ST-elevation myocardial infarction and the relationship between apelin-12 and the neutrophil/lymphocyte ratio in patients undergoing primary coronary intervention

Abstract: We have shown that lower apelin-12 level on admission is associated with higher SYNTAX scores and no-reflow phenomenon and may be used as a prognostic marker for hospital MACE in patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Similar to stable CAD patients, elevated NLR prognosticates adverse outcome in ACS patients as shown by several studies both at short term, i.e., <30 days (88, 89, 91, 9799), and long term, i.e., >6 months, of follow-up (74, 75, 83, 89, 9193, 97, 102) with an average fourfold increased risk. Only in two studies, the NLR was not independently associated with MACE and CVD mortality (87, 90).…”
Section: Neutrophil To Lymphocyte Ratiomentioning
confidence: 75%
“…Similar to stable CAD patients, elevated NLR prognosticates adverse outcome in ACS patients as shown by several studies both at short term, i.e., <30 days (88, 89, 91, 9799), and long term, i.e., >6 months, of follow-up (74, 75, 83, 89, 9193, 97, 102) with an average fourfold increased risk. Only in two studies, the NLR was not independently associated with MACE and CVD mortality (87, 90).…”
Section: Neutrophil To Lymphocyte Ratiomentioning
confidence: 75%
“…Liu and colleagues 36 have demonstrated the effect of serum apelin-12 in predicting 1 year outcomes following pPCI in patients with STEMI. Topuz and colleagues 37 found lower levels of serum apelin-12 predicts higher incidence of in-hospital MACEs after multivariate regression analysis and is more likely in no-reflow versus normal flow group. This is a result of NO-dependent vasodilatation caused by apelin-12 in clinical studies 38 as well as in animal models.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the plasma concentration of apelin-12 after acute myocardial infarction (AMI) is significantly lower than that in the control population [ 15 , 16 ]. Apelin-12 is negatively associated with troponin I levels, high-sensitivity C-reactive protein, neutrophil/lymphocyte ratio, and the rate of MACE, indicating that apelin-12 can serve as a prognostic biomarker for STEMI patients [ 9 , 17 ]. This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%